Skills and Capabilities of Public Health Informatics in Health Workers - Siti Nurhayati; Agnes Fitria W; Saudin Yuniarno; Kuswanto Kuswanto (RADJA PUBLIKA, 2022)
Objectives:To identify skills and capabilities related to public health informatics in health workers who work in public health service institutions, in order to know the informatics-related aspects of the work carried out by public health workers.Method:This research is a quantitative descriptive study with a cross sectional approach. The sampling technique is simple random sampling. The sample was obtained as many as 133 health workers who have been actively working for at least 1 year at the Primary Health Service/Puskesmas or District/City Health Offices in Banyumas Regency, as well as with the main task/work in public health services. The research instrument used is a questionnaire. Data analysis using univariate analysis.Results :Based on the results of the study, the results of the skills and capabilities of use and analysis of data were good (65.4%); system design skills and capabilities are good (53.4%); media design skills and capabilities are good 69.9%; skills and capabilities of routine use of informatics system (66.9%); network maintenance skills and capabilities (60.2%); database administrator capability skills (62.4%). Based on the percentage of the results of the checklist from the question “Which of the following activities are you able to do or do at/for your health institution”, public health workers in general have a higher percentage than sanitarians, nutrition workers, midwives, nurses and doctors.Conclusions: Based on the results of the study, the results of the skills and capabilities of use and analysis of data, system design, media design, routine use of informatics system, network maintenance, and database administrator were good. Public health workers in general have a higher percentage than another health workers who work related to public health services. Suggestions: It is advisable to hold regular training to upgrade and update the skills and capabilities of health workers related to public health informatics, according to the development of information and communication technology utilized. in public health service institutions.